A proposal to manage multi-task dialogs in conversational interfaces - Griol, David; Molina, Jose M. (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2016)
The emergence of smart devices and recent advances in spoken language technology are currently extending the use of conversational interfaces and spoken interaction to perform many tasks. The dialog management task of a conversational interface consists of selecting the next system response considering the user's actions, the dialog history, and the results of accessing the data repositories. In this paper we describe a dialog management technique adapted to multi-task conversational systems. In our proposal, specialized dialog models are used to deal with each specific subtask of dialog objective for which the dialog system has been designed. The practical application of the proposed technique to develop a dialog system acting as a customer support service shows that the use of these specialized dialog models increases the quality and number of successful interactions with the system in comparison with developing a single dialog model.